2014
DOI: 10.1063/1.4884126
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to improved confinement regimes induced by changes in heating in zero-dimensional models for tokamak plasmas

Abstract: It is shown that rapid substantial changes in heating rate can induce transitions to improved energy confinement regimes in zero-dimensional models for tokamak plasma phenomenology. We examine for the first time the effect of step changes in heating rate in the models of E-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…11 and 30 and followed up by theoretical development and improved models. [31][32][33] A further advance of the 0D model was its 1D, five-field extension 10 which, in addition to the drift wave (DW) intensity and zonal flow (ZF) energy, also evolved the mean flow (MF), pressure, and density. Using this model, important new signatures of the transition were recovered and documented in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…11 and 30 and followed up by theoretical development and improved models. [31][32][33] A further advance of the 0D model was its 1D, five-field extension 10 which, in addition to the drift wave (DW) intensity and zonal flow (ZF) energy, also evolved the mean flow (MF), pressure, and density. Using this model, important new signatures of the transition were recovered and documented in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The model (12) for the L-state reduces to the model (11) for the s-state when N = 0 as intended. In (12a) three additional terms have been added when compared with (11).…”
Section: B Modeling the L-statementioning
confidence: 99%
“…The creation of an edge transport barrier formed by a sheared zonal flow is closely related to the L-H transition 3 . Ordinary differential equation (ODE) models for the L-H transition are based on the predator-prey relationship between zonal flow and turbulent flow, and incorporate a potential energy related to the pressure profile as an additional state variable [4][5][6][7][8][9][10][11][12] . Miki et al 13 and Wu et al 14 have both suggested 1D partial differential equation (PDE) models for the L-H transition based on this predator-prey relationship.…”
Section: Introductionmentioning
confidence: 99%
“…These model has been very successful during the last years [20][21][22]. The aim of this paper is to report on the interesting effect of a stepwise increase of the different heating powers on turbulence and confinement by extending [21].…”
Section: Introductionmentioning
confidence: 99%
“…The bifurcation occurs when zonal flow causes a transport barrier (steep temperature gradient) [2][3][4][5][6], to be produced at the edge of the plasma, improving plasma confinement. Zero-dimensional models [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] [7], called MD model, which has one fewer variable for which oscillatory heating was studied in [21]. This distinctive phenomenology may offer a path to future experimental testing of the assumptions of zero-dimensional models, and perhaps distinguishing between them.…”
Section: Introductionmentioning
confidence: 99%